Involvement of Shc in insulin- and epidermal growth factor-induced activation of p21ras. - Pronk, G J (1994)
Shc proteins are phosphorylated on tyrosine residues and associate with growth factor receptor-bound protein 2 (Grb2) upon treatment of cells with epidermal growth factor (EGF) or insulin. We have studied the role of Shc in insulin- and EGF-induced activation of p21ras in NIH 3T3 cells overexpressing human insulin receptors (A14 cells). A14 cells are equally responsive to insulin and EGF with respect to activation of p21ras. Analysis of Shc immunoprecipitates revealed that (i) both insulin and EGF treatment resulted in Shc tyrosine phosphorylation and (ii) Shc antibodies coimmunoprecipitated both Grb2 and mSOS after insulin and EGF treatment. The induction of tyrosine phosphorylation of Shc and the presence of Grb2 and mSOS in Shc immunoprecipitates followed similar time courses, with somewhat higher levels after EGF treatment. In mSOS immunoprecipitates, Shc could be detected as well. Furthermore, Shc immune complexes contained guanine nucleotide exchange activity toward p21ras in vitro. From these results, we conclude that after insulin and EGF treatment, Shc associates with both Grb2 and mSOS and therefore may mediate, at least in part, insulin- and EGF-induced activation of p21ras. In addition, we investigated whether the Grb2-mSOS complex associates with the insulin receptor or with insulin receptor substrate 1 (IRS1). Although we observed association of Grb2 with IRS1, we did not detect complex formation between mSOS and IRS1 in experiments in which the association of mSOS with Shc was readily detectable. Furthermore, whereas EGF treatment resulted in the association of mSOS with the EGF receptor, insulin treatment did not result in the association of mSOS with the insulin receptor. These results indicate that the association of Grb2-nSOS with Shc may be an important event in insulin-induced, mSOS-mediated activation of p21ras.